Social Norms, Cultural Rituals and Moral Baggage: Contrasting Realities for Women in Sunil Gangopadhyay’s Shei Shomoe (Philosophy and Progress, 2021)
The relationship between history and literature is inseparable from the point of view that both disciplines deal with the whole spectrum of human experience. History shapes many a form of literature. Many of the world‘s most celebrated novelists have based their storyline on historical facts. Conversely, historical accounts are known to have been complimented by literary sources. More often than not, womens' historians have to rely on literature when no other sources exist to reconstruct the life of women in a given time frame. Shei Shomoe (Those Days) is one such historical novel by Sunil Gangopadhyay where he captured a vivid picture of the cross currants of social, political and intellectual life in the city of Kolkata in the nineteenth century. The time-frame of the novel is from 1840 to 1870 and that is the time when the Woman‘s Question came to the forefront as a major factor in the discourse on social reform. Sunil Gangopadhyay, in his groundbreaking novel, adds to this discourse with his rare   insight into the lives of women from varied social and class backgrounds to see how they negotiated patriarchal attitudes and defined their own space. This paper is a tribute to Sunil Gangopadhyay‘s efforts to explain the dichotomous relationship between patriarchy and social reform and how womens' lives got caught in the middle.Philosophy and Progress, Vol#65-66-; No#1-2; Jan-Dec 2019 P 179-206